2021
DOI: 10.4103/ajns.ajns_512_20
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome based on trauma and injury severity score, IMPACT and CRASH prognostic models in moderate-to-severe traumatic brain injury in the elderly

Abstract: Objectives: This study aimed to evaluate the trauma and injury severity score (TRISS), IMPACT (international mission for prognosis and analysis of clinical trials), and CRASH (corticosteroid randomization after significant head injury) prognostic models for prediction of outcome after moderate-to-severe traumatic brain injury (TBI) in the elderly following road traffic accident. Design: This was a prospective observational study. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Secondly, it would be interesting to investigate how shifting demographics in trauma cohorts may impact outcome predictions. There is increasing evidence of a shifting demographics with increasing age of TBI-patients, in line with this study, which poses new challenges for the management of TBI, including risk of treatment bias 58 , 70 72 . Thirdly, it would be valuable to investigate the relationship between injury severity, symptoms, and HRQoL, as this study found that they are not always directly related, and further studies are needed to understand how they interact.…”
Section: Discussionsupporting
confidence: 72%
“…Secondly, it would be interesting to investigate how shifting demographics in trauma cohorts may impact outcome predictions. There is increasing evidence of a shifting demographics with increasing age of TBI-patients, in line with this study, which poses new challenges for the management of TBI, including risk of treatment bias 58 , 70 72 . Thirdly, it would be valuable to investigate the relationship between injury severity, symptoms, and HRQoL, as this study found that they are not always directly related, and further studies are needed to understand how they interact.…”
Section: Discussionsupporting
confidence: 72%
“…Up to now, there has not been a widely acknowledged prognostic risk assessment tool for the geriatric TBI. Previous studies have explored the prognostic value of International Mission for Prognosis and Analysis of Clinical Trials in TBI (IMPACT) score and Corticosteroid Randomization after Significant Head Injury (CRASH) score in geriatric TBI patients [33,[42][43][44]. One of them found IMPACT showed moderate discrimination and slight overestimation of the actual outcome for geriatric TBI [42].…”
Section: Discussionmentioning
confidence: 99%